Cinematic Geopolitics of Zombies: Notes for Debate - Brito Alvarado, Xavier (2020)
The zombie has ceased to be the start of low-budget films and has become a scientific concept (biological, social, economic and techonological), a metaphor for the reflection of the varius social problems, in an entity that has gone from human to posthuman, until becoming an antisubject.  The zombie causes fear in two directions: the first, to be devoured by it and, the second, to become one. Its ontological position places it between the subject and the object, breaking the dual models, regardless of gender, socioeconomic statu or geography, so it is the ideal metaphor for contemporany social analysis, where marxist, post cololinal and gender, post structuralist, postmodern, posthumanist theories can dialogue.  From a theoretical approach, from anthropology, sociology and cinema, this essay ponder on the zombie outside the classical reductionist views, which have placed it as a marginal cultural product, intended to satisfy playful momento, contrary to this position, what is intended, rather, is to give a critical view of the zombie and its contemporary social interference.